Local planning for terror and disaster from bioterrorism to earthquakes - (Laura Ann); Cole, Leonard A. 1933- 1906-1998.; Connell, Nancy D. 1952- (Hoboken, N.J. John Wiley & Sons, 2012)
Introduction: the known and the unknown; Healthcare professionals; Institutional management; Support and security.
Includes bibliographical references and index.
Keywords: Emergency management -- Case studies; Disaster relief -- Case studies; Disaster medicine -- Case studies